1994
DOI: 10.1007/bf02648160
|View full text |Cite
|
Sign up to set email alerts
|

On the differential diagnosis of reading, attentional and depressive disorders

Abstract: Children may present with reading and/or attentional and/or affective (depressive) disorders in childhood. Although reading problems are more readily identifiable, childhood attentional and affective disorders can be difficult to recognize and diagnose. Here are discussed a number of complex and potentially confusing ways in which reading, attentional and affective disorders may be related: a primary problem in one area may result in problems in another; one disorder may look like another; and/or a child may s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…The claim that a diagnosis of learning disability is likely to be manifest in both academic delays and severe emotional maladjustments is supported by research literature and clinical practice (Hayes and Sloat 1988;Rourke, Young, and Leenaars 1989;Huntington and Bender 1993;Cohen 1994;Javorsky 1995). Miller (1996) hypothesizes that "children and adults with learning disabilities typically lack specific cognitive prerequisites that other people have, and therefore are especially vulnerable to the effects of failure."…”
mentioning
confidence: 97%
“…The claim that a diagnosis of learning disability is likely to be manifest in both academic delays and severe emotional maladjustments is supported by research literature and clinical practice (Hayes and Sloat 1988;Rourke, Young, and Leenaars 1989;Huntington and Bender 1993;Cohen 1994;Javorsky 1995). Miller (1996) hypothesizes that "children and adults with learning disabilities typically lack specific cognitive prerequisites that other people have, and therefore are especially vulnerable to the effects of failure."…”
mentioning
confidence: 97%
“…A later study (Comings, Gade-Andavolu, Gonzalez, Wu, Muhleman, Chen, et al, 1998) identified 20 such genes, each contributing a small but additive effect in unique combinations for various disorders. The possibility of overlapping categories of diagnosis for a variety of disabilities has also been put forward by Cohen (1994), Stordy (1998) and Anderson (1997), with Parry (1996) hypothesising a multistimuli disorganisation syndrome as outlined in Figure 1 p.26. He claims that such a concept allows for the overlap of symptoms seen clinically, makes better descriptive sense to clinicians and parents, and ensures better prescription for therapy and intervention.…”
Section: Discussionmentioning
confidence: 96%
“…The diagnostic category of ADHD is also hypothesised to include a variety of sub-types (Hazell, 1995;Prior, Sanson, Smart, & Oberklaid, 1995;Edwards & Barkley, 1997). It has further been suggested that there is a substantial overlap in the diagnostic categories of dyslexia and ADHD (Cohen, 1994;Parry, 1996;Reynolds, Elsknin, & Brown, 1996), with the implication that they may have a common neurological or genetic influence (Hay &. Levy, 1996;Silver, 1990).…”
Section: Discussionmentioning
confidence: 98%
“…Considering the high comorbidity of dyslexia and ADHD (Wang & Chung, 2018), most previous studies of children with dyslexia excluded those with ADHD during recruitment to avoid the influence of poor attention. Undeniably, however, children with dyslexia have been demonstrated to have mild attention problems even though they do not meet the diagnostic criteria of ADHD (Cohen, 1994). Thus, we were not surprised to find that the recruited participants with dyslexia in our study showed significantly poor performance on two of the three forms of attention, namely, selective attention and attentional switching.…”
Section: Discussionmentioning
confidence: 99%